Comparison between epidural and opioid analgesia for infants undergoing major abdominal surgery. Issue 8 (23rd June 2019) - Martin, Lizabeth D.; Adams, Trevor L.; Duling, Laura C.; Grigg, Eliot B.; Bosenberg, Adrian; Onchiri, Frankline; Jimenez, Nathalia
Abstract: Background: Epidural analgesia is considered optimal for postoperative pain management after major abdominal surgery. The potential to decrease anesthetic and opioid exposure is particularly desirable for infants, given their vulnerability to respiratory depression and concern for anesthetic neurotoxicity. We reviewed our experience with infants undergoing major abdominal surgery to determine if epidural catheter use decreased anesthetic and opioid exposure and improved postoperative analgesia. Methods: This retrospective cohort study included infants (<12 months) who underwent exploratory laparotomy, ureteral reimplantation, or bladder exstrophy repair between November 2011 and November 2014. Primary outcomes of anesthetic exposure (mean endtidal sevoflurane) and intraoperative opioid administration were compared between infants who received epidural catheters and those who did not. Secondary outcomes included postoperative pain and sedation scores and morphine equivalents administered 0‐24 and 24‐48 hours after surgery. Results: Of 158 eligible infants, 82 were included and 47 received epidurals. Patients with epidurals underwent bladder exstrophy repair (N = 9), ureteral reimplantation (N = 8), and exploratory laparotomy (N = 30). Infants with epidurals received less intraoperative fentanyl (2.6 mcg/kg (0, 4.5) vs 3.3 mcg/kg (2.4, 5.8), P  = 0.019) and morphine (6% (3/47) vs 26% (9/35), P  = 0.014) in univariate analysis. After controlling for age and emergency surgery, differences in long‐acting opioid administration persisted, with significantly less morphine given in the epidural group (OR 0.181; 95% CI 0.035‐0.925; P  = 0.040). Mean endtidal sevoflurane concentrations were similar between groups. There was no significant difference in postoperative median morphine equivalents. Conclusion: Placement of epidural catheters in infants undergoing major abdominal surgery is associated with decreased long‐acting opioid requirements intraoperatively. Epidural placement does not preclude opioid exposure however, as opioids may be administered for indications other than nociceptive pain in the difficult‐to‐assess postoperative infant. Further prospective studies are warranted to better quantify the effect of epidural analgesia on intraoperative anesthetic exposure in infants.